Private credit in dual banking countries: does bank ownership type matter? - Noordin, Nazrul Hazizi; Mohid Rasid, Mohamed Eskandar Shah; Ibrahim, Mansor H. (John Wiley & Sons, Inc., 2022)
This study investigates how the effects of government and foreign bank ownership on private credit vary in the cases of Islamic and conventional banks using data extended from Claessens and van Horen (2014) of 29 dual banking countries from 1995 to 2017. In support of the political view of financial development, we find that the presence of state-owned Islamic banks seem to be slightly less harmful to private credit flows than their conventional peers, particularly in the period after the global financial crisis. We also document evidence showing that countries with a larger foreign Islamic bank presence tend to have deeper credit markets post-crisis. However, such advantages may often be outweighed by the costs associated with increased penetration by foreign conventional banks.